Heat transfer of the TiO2/water nanofluid in an annulus of the finite rotating cylinders - Rahman, M. R. A. (International Information and Engineering Technology Association, 2018)
Study on the heat transfer of TiO2/water nanofluid flows inside annulus of the finite rotating cylinders was done numerically. Inner shaft and outer tube were rotated in co-rotating and counter-rotating direction. The k-epsilon turbulent model and the Mixture-multiphase model were used to treats the turbulence flow and the multiphase flows of the TiO2/water nanofluid, respectively. Results of the current work are in agreement with published work. Results showed that increased in Reynolds number the Nusselt number increases. The distribution of the Nusselt number at the specific location along the heated inner shaft for co-rotating and counter-rotating cases shows a different distribution profile. The counter-rotating case was found to be more efficient in enhancing the heat transfer rate in comparison to the co-rotating case. This observation is suggested because of the boundary layers disturbances that originate from the additional vortices produced by the competing rotational speed between inner shaft and outer tube.